2017
DOI: 10.15626/eco-tech.2010.051
|View full text |Cite
|
Sign up to set email alerts
|

LCA of Local Bio-chp Fuelled Greeenhouses Versus Mediterranean Open Fiel Tomatoes for Consumption in Northern Scandinavia

Abstract: Tomatoes are a commonly used product in the Scandinavian countries, where locally grown tomatoes generally have to be cultivated in greenhouses, heated for most part of the year. Tomatoes imported from the Mediterranean area will not need heated greenhouses, but are transported a longer distance. Earlier studies have shown imported tomatoes over long distances are environmentally preferable when compared to tomatoes produced in greenhouses. In this study, tomatoes for the Trøndelag market in Norway locally gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…Horticultural LCA studies in northern Europe comparing field production to greenhouse technologies have found that when co-generation or waste heat energy sources were used as the greenhouse energy source, environmental results were better than for field-grown food imported from more remote locations (Nordenström et al, 2010). Using solar PV technology for cooling and baseload energy in the present study produced similar results for several environmental indicators.…”
Section: Horticultural Systemsupporting
confidence: 63%
“…Horticultural LCA studies in northern Europe comparing field production to greenhouse technologies have found that when co-generation or waste heat energy sources were used as the greenhouse energy source, environmental results were better than for field-grown food imported from more remote locations (Nordenström et al, 2010). Using solar PV technology for cooling and baseload energy in the present study produced similar results for several environmental indicators.…”
Section: Horticultural Systemsupporting
confidence: 63%
“…A commercial waste management company (SUEZ, 2017) combined a waste incineration plant with a tomato greenhouse in France, using the generated heat energy to control the growing environment, achieving operational emissions reduction of around 1 kg CO2 per kg of tomato. Similar environmental benefits have been obtained by co-locating tomato greenhouse production with a micro CHP gasification plant fueled by forest residues in Norway (Nordenström et al, 2010). Exploiting the availability of urban organic waste, a pilot project in Ohio integrated small-scale AD units in a hydroponic greenhouse, using digestate as fertilizer and the greenhouse heat to operate the mesophilic AD unit (Davis, personal communication, May 2, 2018).…”
Section: Iv) Synergistic Benefits Through On-site Integration With Wamentioning
confidence: 93%
“…). These datasets were obtained from published literature and from the Global Biodiversity Information Facility …”
Section: Methodsmentioning
confidence: 99%